Child support liability and partnership dissolution - Ian Walker; Yu Zhu (Institute for Fiscal Studies (IFS), 2004)
This paper studies the determinants of partnership dissolution and focuses on the role of child support. We exploit the variation in child support liabilities driven by an important UK policy reform to separately identify the effects of children from the effect of child support liability. We find strong evidence that an increase in the child support liability significantly reduces dissolution risk. Our results suggest that child support criteria that are based on the non-custodial parent's income, compared to criteria based on aggregate incomes of both parents, would imply much smaller separation rates.
Keywords: D13; D31; J12; J13; J16; 330; partnership dissolution; child support; empty nest effect; Unterhaltsrecht; Familienrecht; Großbritannien; Rechtsreform